Plato's Essentialism : Reinterpreting the Theory of Forms - Politēs, Basileios (University of Cambridge ESOL Examinations, 2021)
Cover -- Half-title -- Title page -- Copyright information -- Dedication -- Contents -- Acknowledgements -- Introduction -- Addendum -- Chapter 1 Why cannot the ti esti question be answered by example and exemplar?: Hippias Major -- Chapter 2 Why cannot essences, or Forms, be perceived by the senses?: Hippias Major. Phaedo. Republic -- 2.1 Problems with the standard answer, and in defence of a very different answer -- 2.2 The origin of this answer in the Hippias Major -- 2.3 This is what is behind the claim in the Phaedo that essences and Forms cannot be perceived by the senses -- 2.4 From beautiful to equal and one -- 2.5 From beautiful, equal and one to human and bed -- 2.6 What about numbers? Does Plato's argument extend to them? -- 2.7 That Forms cannot be perceived by the senses does not imply that they can be known only a priori -- Chapter 3 Why are essences, or Forms, unitary, uniform and non-composite? Why are they changeless? Eternal? Are they logically independent of each other?: Phaedo and Republic -- 3.1 The unity, uniformity and non-compositeness of Forms -- 3.1.1 A false start -- 3.1.2 Unitary accounts and unitary things -- 3.2 Plato's reasoning for the claim that Forms are unitary, uniform and non-composite -- 3.3 Are Forms logically independent of each other? -- 3.4 The changelessness and the eternality of Forms -- 3.5 A false start, on the changelessness of Forms -- 3.6 Plato's reasoning for the claim that Forms are changeless -- 3.7 Whether the eternality of Forms can be defended in a similar way -- Chapter 4 The relation between knowledge and enquiry in the Phaedo -- 4.1 Two seemingly conflicting epistemological claims in the Phaedo -- 4.2 Why sense-perception is necessary to think of a Form -- 4.3 How to reconcile the two epistemological claims in the Phaedo.